Exploring participatory culture among persons with disability: a case study on #stopaudism - Ikrima Nurfikria (Jurnal Studi Komunikasi, 2023)
Abstract This study examines the participatory culture of persons with disabilities in Indonesia by analysing their engagement in hashtag activism on Instagram. The selected hashtag, #stopaudism, gained prominence in response to an incident involving the Minister of Social Affairs, Tri Rismaharini, who compelled Deaf persons to speak during an event commemorating the National Day of Disabilities on 1 December 2021. This research employs a mixed-method approach, combining web scraping techniques with thematic analysis, and draws upon Henry Jenkins's participatory culture theory to analyse Instagram posts featuring the #stopaudism hashtag by persons with disabilities. The web scraping techniques successfully tracked trends in the #stopaudism hashtag, revealing a notable surge on December 2nd and 3rd, 2021, and highlighted posts with the highest likes and comments. Thematic analysis unveiled six strategies employed by persons with disabilities on Instagram to participate actively in hashtag activism: education, self-disclosure, declaration of hashtag activism, expression of anger or disappointment, presentation of evidence/media coverage, and invitations to sign petitions.